Social Reward Questionnaire (SRQ): development and validation - Foulkes, Lucy; Viding, Essi; McCrory, Eamon J.; Neumann, Craig S. (Frontiers in Psychology, 2014)
Human beings seek out social interactions as a source of reward. To date, there have been limited attempts to identify different forms of social reward, and little is known about how the value of social rewards might vary between individuals. This study aimed to address both these issues by developing the Social Reward Questionnaire (SRQ), a measure of individual differences in the value of different social rewards. Exploratory factor analysis (EFA) was run on an initial set of 75 items (N=305). Based on this analysis, confirmatory factor analysis (CFA) was then conducted on a second sample (N=505) with a refined 23-item scale. This analysis was used to test a six-factor structure, which resulted in good model fit (CFI=.96, RSMEA=.07). The factors represent six subscales of social reward defined as follows: Admiration; Negative Social Potency; Passivity; Prosocial Interactions; Sexual Reward; and Sociability. All subscales demonstrated good test-retest reliability and internal consistency. Each subscale also showed a distinct pattern of associations with external correlates measuring personality traits, attitudes and goals, thus demonstrating construct validity. Taken together, the findings suggest that the SRQ is a reliable, valid measure that can be used to assess individual differences in the value experienced from different social rewards.